99mTc-Trimethyl-BrIDA-Szintigraphie bei HIV-bedingter Cholangiopathie - Bair, H.-J.; Behr, Th.; Rubbert, Andrea; Becker, W.; Wolf, F. (Nuklearmedizin - NuclearMedicine, 1995)
A HIV-infected 37-year-old man with diffuse mid-abdominal pain and elevated liver enzymes was sequentially studied by sonography, computed tomography (CT), 99mTc-trimethyl-BrlDA scintigraphy and endoscopic retrograde cholangiopancreatography (ERCP). CT and sonography did not lead to a final diagnosis. Cholescintigraphy showed signs of cholecystitis and sclerosing cholangitis with intra- and extrahepatic bile duct dilatation. These findings could be confirmed by ERCP, rendering HIV-associated cholepathy probable. Cytomegalovirus infection was demonstrated by polymerase chain reaction from bile fluid and the presence of Cryptosporidia infection in a histology specimen isolated by ERCP. Therefore, biliary scintigraphy seems promising for screening for HIV-associated cholangio-and cholecystopathy, being less invasive and less bothering for the patient than ERCP.
Keywords: HIV-related cholangiopathy; Cryptosporidia and cytomegalovirus infection; biliary scanning; ERCP